FOUR - Palijama, Tirza Viona; Ardini, Ni Wayan; Laksmi, Desak Made Suarti (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
FOUR is a composition inspired by the anxiety experienced by the composer. This work tells about the unrest experienced by the composer after his late father passed away on June 4, 2023. The composer felt a lot of emptiness and confusion in continuing his life after being left by his father. The efforts made to get through this grief, ended up returning to the same place and rotating only there. In this composition, the composer uses the concept of minimalist music, which has minimal musical elements with phrases that have a lot of repetition. This repetition interprets how the composer's life only revolves and returns to the same feeling of emptiness and confusion. In this composition, the composer has a musical form and structure with A, B, and A' charts. In the beginning, it interprets the confusion experienced by the composer, B interprets the emotions experienced by the composer, and A' interprets how the composer's efforts only lead back to the same place. The reference of this work is;